Effectiveness of Health Education Methods on Awareness and Compliance of Iron Tablet Consumption in Adolescent Girls - Anjaya, Aisy; Alyani, Ajeng; Nugrahani, Nadia; Fakhrunnisa, Raissa; Herbawani, Chahya (Miracle Journal of Public Health, 2024)
Anemia in adolescent girls is a global health problem with a prevalence of 30%, while in Indonesia, the figure reaches 48.9%, which is mostly caused by iron deficiency. One of the efforts to prevent and manage anemia in adolescent girls is through health education on consuming Blood Additive Tablets (TTD). This study aims to evaluate the effectiveness of health education methods in increasing awareness and adherence of adolescent girls to the consumption of TTD. The study used a systematic review method with PRISMA guidelines. Literature was obtained from online databases such as ScienceDirect, Google Scholar, and ResearchGate, which were selected based on inclusion and exclusion criteria. Of the ten articles analyzed, it was found that health education methods significantly improved adolescent girls' awareness and adherence to TTD consumption. An approach that combines lectures with media, such as PowerPoint presentations, videos, and demonstrations (mixed media education intervention program), effectively improved adolescents' knowledge and behavior regarding TTD.